Employee Engagement in SME in Kuala Lumpur - Tan, Kai Mian (2016)
Employee engagement involve the direct communication with the elements from Human Resources, Sales, Marketing and Public Relation, it needs to be centralized then the organization can launch the employee engagement programs and strategies to improve the business performance (Horney, 2015). Based on McConnell (2011) research paper, engaged employees basically more productive and less likely to leave their organizations compared to disengaged employees. According to Malaysia statistics report in 2014, SME industry contributed 35.9% to Malaysia’s GDP. Therefore, the purpose of this research was to examine the relationship between employee engagement with working relationship, empowerment, employee motivation, employee retention and work life balance. A sample of 123 employees, based on convenience sampling was chosen to collect information using a self-administrated questionnaire that was adopted. The findings indicated that working relationship, empowerment, employee motivation, employee retention and work life balance have positive relationship with employee engagement. Lastly, based on the findings, this research proposed measures to improve the competitiveness of SME in Kuala Lumpur, Malaysia via appropriate employee engagement programs.